Peran Santri Dalam Perputaran Perekonomian Pondok Pesantren Raden Rahmad Sunan Ampel Jember - Muhammad Faisal Azka; ‘Ainuz Zubaid Syafi’ul ‘Aziz (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
As the main community within the scope of Islamic boarding schools. the role of the santri, who daily seek religious knowledge, is still needed for the sustainability of the institutional economy to meet future needs. By forming an entrepreneurship program that facilitates students, they will learn directly in the world of business by selling food products. it is also wrong to support the needs of the institution in the future. the purpose of conducting this research is to find out what efforts are made on the role of santri in the economic cycle of Islamic boarding schools. This study uses qualitative research methods with an ethnographic approach. and the theoretical basis used as an analytical knife is the structural-functional theory put forward by Talcot Parson. data collection using interviews, observation and documentation